2019
DOI: 10.1128/jcm.01304-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Utilities of Different Multilocus Sequence Typing Schemes for Identifying Outbreak Strains of Mycobacterium abscessus subsp. massiliense

Abstract: Outbreaks of infections by Mycobacterium abscessus, particularly subspecies massiliense, are increasingly reported worldwide. Several multilocus sequence typing (MLST) protocols for grouping international outbreak strains have been developed but not yet directly compared. Using the three-gene (hsp65, rpoB, and secA1), seven-gene (argH, cya, glpK, gnd, murC, pta, and purH) and thirteen-gene (all of the preceding genes plus gdhA, pgm, and pknA) MLST schemes, we identified 22, 38, and 40 unique sequence types (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…Nevertheless, MLST as previously used by T ettelin et al [ 18 ] to cluster MAB-m outbreak strains, has been validated by WGS [ 19 ]. In addition, MLST as used by T ettelin et al [ 18 ] has been shown to be in high agreement with the MLST scheme used here [ 40 ]. As MLST is more accessible than WGS to the developing world, and the MLST scheme used here is publicly available on the Pasteur Institute's database unlike the scheme of T ettelin et al [ 18 ], most studies conducted from 2014 onwards have used this scheme ( table 4 ) [ 40 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, MLST as previously used by T ettelin et al [ 18 ] to cluster MAB-m outbreak strains, has been validated by WGS [ 19 ]. In addition, MLST as used by T ettelin et al [ 18 ] has been shown to be in high agreement with the MLST scheme used here [ 40 ]. As MLST is more accessible than WGS to the developing world, and the MLST scheme used here is publicly available on the Pasteur Institute's database unlike the scheme of T ettelin et al [ 18 ], most studies conducted from 2014 onwards have used this scheme ( table 4 ) [ 40 ].…”
Section: Discussionsupporting
confidence: 68%
“…In addition, MLST as used by Tettelin et al has been shown to be in high agreement with the MLST scheme used here [40]. Since MLST is more accessible than WGS to the developing world, and the MLST scheme used here is publicly available on the Institut Pasteur's database unlike Tettelin's scheme, most studies conducted from 2014 onwards have used this scheme (Table 4) [18,40].…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies showed that genetic changes by sequence analysis of rpoB, hsp65, secA1 , 23S rrl and erm (41) genes accomplish classifying subspecies and specific antibiotics resistance accurately. 272829 Marras et al 30 reported that a real-time multiplex PCR assay approach using molecular beacons could identify all genotypes that affect susceptibility, and thus shortened the treatment guidance to less than three hours. Additional reagents and reaction time are both needed for subspecies identification and detection of antibiotic resistance when using genetic tests.…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular outbreak investigations, source tracking, and population structure analyses of Mab have mainly been performed by repetitive sequence-PCR (rep-PCR), random amplified polymorphic DNA typing (RAPD PCR), multi-locus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) and core genome single nucleotide polymorphism (cgSNP) analysis 4,[27][28][29] . While cgSNP clearly offers the highest resolution for outbreak investigations, the lack of standardized bioinformatic pipelines and nomenclature scheme limits the application to individual retrospective investigations [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%